Preparation and characterization of smart polymer gel for self-healable electronics - Chua, Yi Suan (2018)
Self-healing materials have been researched widely over the years due to its inherent healing abilities. Especially with the advancement of technology, the development for self-healable electronics is on the rise so that mechanical damage such as strains and cracks could be repaired to enhance the durability of such devices. Here, the project focuses on the development of the self-healing dielectric material which posses the properties of the resistive random access memory (ReRAM) device. The dielectric layer that consists of poly(acrylic acid) (PAA) and poly(vinyl alcohol) (PVA) was demonstrated as a self-healing dielectric layer through the experimental process of self-healing test. Multiple tests under various conditions were conducted to obtain the ideal self-healing composition. To achieve memory properties, silver nitrate (AgNO3) was incorporated into the polymer matrix. Electrical characterization was then executed and voltages were applied to obtain the IV graph, which illustrates the characteristics of the PAA-PVA-AgNO3 dielectric layer.